Comprehensive multi-omics analysis identifies chromatin regulator-related signatures and TFF1 as a therapeutic target in lung adenocarcinoma through a 429-combination machine learning approach - Fan, Jun; Chen, BoGuang; Wu, Hao; Liang, Xiaoqing; Shen, Wen; Miao, Xiaye (Frontiers in Immunology, 2024)
Lung cancer is a leading cause of cancer-related deaths, with its incidence on the rise. Chromatin remodeling, a key process in gene expression, plays a vital role in the development and progression of malignant tumors. This study highlights the role of chromatin regulators (CRs) in lung adenocarcinoma (LUAD) and introduces a novel prognostic model. Using a 429-combination machine learning approach, we developed a chromatin regulator-related signature (CRRS) that accurately predicts survival outcomes in LUAD patients, validated across multiple independent datasets. CRRS was also found to influence the immune microenvironment, affecting immune cell infiltration in LUAD. High-risk patients showed increased activity in cell cycle and DNA repair processes, with significant differences in mutations and immune responses compared to low-risk patients. Among the identified chromatin regulators, TFF1 emerged as a promising therapeutic target. To confirm its role, we used siRNA to reduce TFF1 expression in LUAD cells, followed by apoptosis analysis, proliferation assays, and in vivo tumor growth studies. Further tests, including Ki67 expression and TUNEL assays, confirmed the impact of TFF1 on tumor growth and cell death. These findings suggest that TFF1 is a key target for new treatment strategies in LUAD.